STEAM and Environment on students' creative-thinking skills: A meta-analysis study. Issue 1 (February 2021) - Suganda, Emma; Latifah, Sri; Irwandani,; Sari, Putri Mardiana; Rahmayanti, Henita; Ichsan, Ilmi Zajuli; Mehadi Rahman, Md.
Abstract: In the 21 st -century, learning based on Science, Technology, Engineering, Art, and Mathematics (STEAM) has been increasingly popular, especially in learning physics at schools. This learning is considered to be able to accommodate many students' abilities, especially in the aspects of understanding and higher-order thinking skills. Through a meta-analysis study, this article discusses how STEAM learning accommodated students' creative-thinking skills. The study was carried out by collecting articles in the Scopus, DOAJ, and ERIC databases. A total of 16 selected articles based on STEAM and creative-thinking skills keywords were analyzed through 5 stages, namely orientation, conceptualization, investigation, discussion, and conclusion. The results of the analysis showed that STEAM learning can improve students' creative-thinking skills. STEAM can be integrated with environment concept. However, research on STEAM and creative-thinking skills has not been done much in the field of physics.